ANALISIS TINGKAT KEPUASAAN PENGGUNA APLIKASI SHOPEE DIKALANGAN GEN Z MENGGUNAKAN REGRESI SEDERHANA - Juwita, Ratna; Roswati, Roswati; Sutabri, Tata (Universitas Majalengka, 2024)
This research aims to analyze the level of satisfaction of Shopee application users among generation Z (Gen Z) using a simple regression method. In the ever-growing digital era, Shopee has become one of the most popular e-commerce platforms in Indonesia, especially among Gen Z who are very familiar with technology. This research uses primary data collected through an online survey of 30 Gen Z respondents who are active users of the Shopee application. The independent variables used in this research include ease of use, product variety, customer service quality, and promotions. The dependent variable measured is the level of user satisfaction. The results of simple regression analysis show that all independent variables have a positive and significant influence on the level of satisfaction of Shopee application users among Gen Z. The customer service quality variable has the most dominant influence, followed by ease of use, promotions and product variety. The findings of this research provide practical implications for Shopee management in improving marketing strategies and service quality to maintain and increase user satisfaction among Gen Z. This research also provides academic contributions by adding insight into the factors that influence e-commerce user satisfaction among this generation. young. This abstract provides a brief but comprehensive overview of the aims, methods, results and implications of the research conducted, in accordance with academic journal writing standards.